IDENTITAS DIRI DAN HIPEREALITAS DALAM MEDIA SOSIAL - Emi Widiyanti; Seto Herwandito (Cakrawala Jurnal Penelitian Sosial, 2018)
The ‘Update Status’ phenomenon is a popular phenomenon among millennials. In the city of Solo the update status is much done around the world of food or culinary. Eating is no longer a necessity of life, but it has shifted to a lifestyle for young people. Where to share pictures around the café or food served on their social media becomes an important moment. Describe what they eat and where they eat, by utilizing social media as if they want to show their social status. This article will discuss how the phenomenon updates the culinary status among young people by appearing at their forms of status updates, then review the extent of their association with their identity reforming both real identity and virtual identity them and the end will try to peel the theory of hipperreality from Jean P. Baudrillard.. The method applied is an in-depth interview with the total participants 10 people. With the bulk of participants are students (millennials). The results gathered from social media were used by netizens as a space to express themselves, substitutes for face-to-face forms. There is a negative and positive impact from this phenomenon, Negative impact is the emergence of the consumption society that no longer consumes goods and services, but more on consuming the brand, while positive impact is and moving the economy of an area with the increase of public consumption of goods and services.